Satu Kasus Langka: Harlequin Ichthyosis - I Gusti Ayu Sattwika Pramita; Ni Luh Putu Ratih Vibriyanti Karna (Intisari Sains Medis, 2021)
Introduction: Harlequin ichthyosis is a genetic skin disease due to mutations in the ABCA12 gene inherited in an autosomal recessive manner. It is a severe form of ichthyosis characterized by a distinct clinical appearance of a thick stratum corneum. Harlequin ichthyosis is rarely found, and patients generally die a few days after birth.Case description: We reported a baby girl aged one day with thick and cracked skin since birth. Physical examination revealed eclabium, ectropion, microtia, hyperflexion of the arms and legs, and hypoplasia of the fingers and toes. Dermatological examination showed thick yellowish-white scales separated by deep and erythematous fissures. The patient was placed in an incubator and was given supportive care, including nutrition and fluid through an orogastric tube, oleum olivarum as a moisturizer, gentamicin cream 0.1%, and gentamicin eye ointment 0.3%. The patient died after 21 days of treatment.Conclusion: Harlequin ichthyosis has a poor prognosis and a high mortality rate due to impaired skin barrier functions that lead to dehydration, impaired thermoregulation, respiratory problems, and infections. Management of harlequin ichthyosis needs a multidisciplinary team and supportive care, consisting of fluid, electrolyte, and nutrition management, maintaining skin hydration, eye care, and preventing respiratory failure or sepsis.  Pendahuluan: Harlequin ichthyosis adalah penyakit kulit genetik yang diturunkan secara resesif autosomal dan merupakan bentuk berat dari iktiosis akibat adanya mutasi pada gen ABCA12. Penyakit ini ditandai dengan adanya gambaran klinis yang khas berupa penebalan stratum korneum. Harlequin ichthyosis jarang ditemukan dan umumnya pasien meninggal beberapa hari setelah kelahiran.Kasus: Dilaporkan seorang bayi perempuan berumur 1 hari dengan keluhan kulit tebal dan pecah-pecah sejak lahir. Pada pemeriksaan fisik ditemukan eklabium, ektropion, mikrotia, hiperfleksi lengan dan kaki, serta hipoplasia jari-jari tangan dan kaki. Berdasarkan pemeriksaan status dermatologikus didapatkan skuama tebal berwarna putih kekuningan yang dipisahkan fisura. Pasien diberikan perawatan suportif berupa perawatan dalam inkubator, pemberian nutrisi melalui OGT, pelembab topikal oleum olivarum, antibiotik topikal gentamisin krim 0,1 %, dan salep mata gentamisin 0,3%.  Pasien meninggal setelah perawatan selama 21 hari. Simpulan: Harlequin ichthyosis memiliki prognosis yang buruk dan angka kematian yang tinggi akibat gangguan dari barier kulit yang menyebabkan dehidrasi, gangguan termoregulasi, gangguan nafas dan infeksi. Penatalaksanaan pasien harlequin ichthyosis adalah multidisiplin dan bersifat suportif, terdiri atas manajemen cairan dan elektrolit, perawatan secara intensif dalam inkubator, pemberian nutrisi, menjaga hidrasi kulit, perawatan mata, dan pencegahan terjadinya gangguan napas, atau sepsis.